2019
DOI: 10.1007/s00431-019-03386-9
|View full text |Cite
|
Sign up to set email alerts
|

Admission hypothermia, neonatal morbidity, and mortality: evaluation of a multicenter cohort of very low birth weight preterm infants according to relative performance of the center

Abstract: This prospective cohort study aimed to assess the association of admission hypothermia (AH) with death and/or major neonatal morbidities among very low birth weight (VLBW) preterm infants based on the relative performance of 20 centers of the Brazilian Network of Neonatal Research. This is a retrospective analysis of prospectively collected data using the database registry of the Brazilian Network on Neonatal Research. Center performance was defined by the relative mortality rate using conditional inference tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Mohamed et al [ 9 ] found the hypothermia is associated with mortality (OR = 1.89; 1.72–2.09), intra-ventricular hemorrhage (OR = 1.86; 1.09–3.14), bronchopulmonary dysplasia (OR = 1.28; 1.16–1.40) or neonatal sepsis (OR = 1.47; 1.09–2.49), and retinopathy of prematurity (OR = 1.45; 1.28–1.72). Similar results were found in other studies [ 10 ]. Laptook et al [ 11 ] found in an adjusted analysis that with each 1 °C decrease in body temperature, sepsis and mortality risks increase by 11 and 28%, respectively.…”
Section: Introductionsupporting
confidence: 93%
“…Mohamed et al [ 9 ] found the hypothermia is associated with mortality (OR = 1.89; 1.72–2.09), intra-ventricular hemorrhage (OR = 1.86; 1.09–3.14), bronchopulmonary dysplasia (OR = 1.28; 1.16–1.40) or neonatal sepsis (OR = 1.47; 1.09–2.49), and retinopathy of prematurity (OR = 1.45; 1.28–1.72). Similar results were found in other studies [ 10 ]. Laptook et al [ 11 ] found in an adjusted analysis that with each 1 °C decrease in body temperature, sepsis and mortality risks increase by 11 and 28%, respectively.…”
Section: Introductionsupporting
confidence: 93%
“…In this cohort, most admitted newborns with measured temperatures were moderately hypothermic, noted in approximately two thirds of those who died. A recent study from Brazil showed that admission hypothermia was significantly associated with early neonatal deaths even in a presence of good quality newborn care [31]. Continuous improvement of thermal care immediately after birth is critically needed.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show a twofold higher hazard of dying among hypothermic newborns at admission. Siqueira and colleagues also showed that hypothermia at admission was significantly associated with early neonatal death even in the presence of high-quality neonatal care [ 61 ].…”
Section: Discussionmentioning
confidence: 99%